2020
DOI: 10.1007/s13199-020-00677-w
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium solani induces the formation of agarwood in Gyrinops versteegii (Gilg.) Domke branches

Abstract: Agarwood is a resinous wood produced by some members of plant family Thymelaeaceae under certain conditions. Agarwood is highly prized, but its formation requires a long-time process in nature. Therefore, various induction techniques have been explored to hasten the process. In this study, we induced agarwood in Gyrinops versteegii, one of the most abundant agarwood-producing trees in Indonesia. We used 12 trees and wounded four branches on each tree through an injection process. We used two strains of the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…However, no prior studies have reported that Mucor and Trichosporon are associated with the formation of agarwood. This important finding has further extended the existing list of fungal genera that had previously been discovered in several agarwood studies (Subasinghe et al 2012;Faizal et al 2020). Moreover, extended studies on bacterial isolation and identification from naturally infected agarwood trees may also be conducted to produce a variety of local microbial inoculants that have the potential to induce agarwood formation in uninfected Aquilaria.…”
Section: Isolation and Identification Of Fungimentioning
confidence: 57%
See 2 more Smart Citations
“…However, no prior studies have reported that Mucor and Trichosporon are associated with the formation of agarwood. This important finding has further extended the existing list of fungal genera that had previously been discovered in several agarwood studies (Subasinghe et al 2012;Faizal et al 2020). Moreover, extended studies on bacterial isolation and identification from naturally infected agarwood trees may also be conducted to produce a variety of local microbial inoculants that have the potential to induce agarwood formation in uninfected Aquilaria.…”
Section: Isolation and Identification Of Fungimentioning
confidence: 57%
“…Four genera of fungal strains were isolated and identified as Aspergillus, Fusarium, Mucor, and Trichosporon (Table 6, Figure 2). Many studies have identified several genera of fungi that are associated with agarwood formation including Aspergillus and Fusarium (Subasinghe et al 2012;Faizal et al 2020). In this study, a different Aspergillus sp.…”
Section: Isolation and Identification Of Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Commercially available liquid medium formulations for agarwood induction are limited and pricey, with tree genotype and environmental factors strongly influencing agarwood induction response and quality (Naziz et al 2019). Endophytic fungi have been employed as a biological inducer for agarwood formation with promising results (Faizal et al 2020, Justin et al 2020. Various species of fungi including Fusarium sp.…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium spp. are endophytic fungi which known to have an important role in agarwood formation ( Faizal et al., 2020 ; Subasinghe et al., 2019 ; Tian et al., 2013 ; Mohamed et al., 2010 ). To our knowledge, though, no studies of agarwood production in A. malaccensis shoot cultures have been performed.…”
Section: Introductionmentioning
confidence: 99%